2011
DOI: 10.1021/jm200386s
|View full text |Cite
|
Sign up to set email alerts
|

Phospshoinositide 3-Kinase (PI3K)/Mammalian Target of Rapamycin (mTOR) Dual Inhibitors: Discovery and Structure–Activity Relationships of a Series of Quinoline and Quinoxaline Derivatives

Abstract: The phosphoinositide 3-kinase (PI3K) family catalyzes the ATP-dependent phosphorylation of the 3'-hydroxyl group of phosphatidylinositols and plays an important role in cell growth and survival. There is abundant evidence demonstrating that PI3K signaling is dysregulated in many human cancers, suggesting that therapeutics targeting the PI3K pathway may have utility for the treatment of cancer. Our efforts to identify potent, efficacious, and orally available PI3K/mammalian target of rapamycin (mTOR) dual inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 16 publications
(22 reference statements)
0
40
0
Order By: Relevance
“…Nishimura et al [77] reported the discovery of a series of substituted quinolines and quinoxalines derivatives (215-217), as potent PI3K/mTOR dual inhibitors (e.g. 203, PI3Kα Ki = 0.6 nM) with excellent pharmacokinetic properties and in vivo efficacies, using compound (214) as the lead.…”
Section: Pyridines Quinolines Indoles and Indazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nishimura et al [77] reported the discovery of a series of substituted quinolines and quinoxalines derivatives (215-217), as potent PI3K/mTOR dual inhibitors (e.g. 203, PI3Kα Ki = 0.6 nM) with excellent pharmacokinetic properties and in vivo efficacies, using compound (214) as the lead.…”
Section: Pyridines Quinolines Indoles and Indazolesmentioning
confidence: 99%
“…Initially, analogues with 6, 6-bicyclic heterocycles (quinoline, isoquinoline, quinoxaline, quinazoline, cinnoline, and naphthyridine) were designed, to replace the benzothiazole, as hinge linker binder. Then by incorporating suitable substituents at the 4-position of the quinoline or the 3-position of the quinoxaline rings, excellent cellular potencies were achieved, which indicated that the ribose pocket of the enzyme can be effectively utilized in optimizing both the potency and the physicochemical properties of PI3K inhibitors [77] .…”
Section: Pyridines Quinolines Indoles and Indazolesmentioning
confidence: 99%
“…However, most of the experimental drugs were designed as inhibitors of tyrosine kinases [219]. Interestingly, the presence of the scaffold in natural sources is higher than those with scaffolds 3 or 4.…”
Section: Quinoxalinesmentioning
confidence: 99%
“…With substantial structural and biochemical information of PI3K inhibitors available, we searched a number of X-ray co-crystal structures of PI3K subunits bound to small molecule inhibitors and explored the binding modes at the ATP-binding site. [20,[28][29][30][31] The active sites of PI3K subunits were mainly comprised of three key regions: the hinge binder, the affinity pocket 3L08). (C) Sequence alignment between PI3Kα, β, γ and δ.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][34][35][36][37][38][39][40][41] Crystallographic analysis found that this scaffold fits the active site very well and thus possesses a high ligand efficiency (LE). As shown in Figure 2(B), the quinoline nitrogen forms a hydrogen bond interaction with Val882 (Val851 in PI3Kα) in the hinge binder region of the kinase domain of PI3Kγ.…”
Section: Introductionmentioning
confidence: 99%